2009
DOI: 10.1037/a0016216
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of the categorization of multidimensional stimuli: I. Unidimensional classification does not necessarily imply analytic processing; evidence from pigeons (Columba livia), squirrels (Sciurus carolinensis), and humans (Homo sapiens).

Abstract: Pigeons (Columba livia), gray squirrels (Sciurus carolinensis), and undergraduates (Homo sapiens) learned discrimination tasks involving multiple mutually redundant dimensions. First, pigeons and undergraduates learned conditional discriminations between stimuli composed of three spatially separated dimensions, after first learning to discriminate the individual elements of the stimuli. When subsequently tested with stimuli in which one of the dimensions took an anomalous value, the majority of both species ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
51
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 39 publications
(81 reference statements)
6
51
1
Order By: Relevance
“…Our results do not support Smith et al’s (2012) analysis of pigeons’ cognitive capacities (see also Lea & Wills, 2008, Lea et al, 2009, and Wills et al, 2009, for further results and discussion). The mere fact that pigeons learned rule-based and information-integration tasks at similar rates does not prove that pigeons are incapable of selective attention.…”
Section: Discussioncontrasting
confidence: 90%
“…Our results do not support Smith et al’s (2012) analysis of pigeons’ cognitive capacities (see also Lea & Wills, 2008, Lea et al, 2009, and Wills et al, 2009, for further results and discussion). The mere fact that pigeons learned rule-based and information-integration tasks at similar rates does not prove that pigeons are incapable of selective attention.…”
Section: Discussioncontrasting
confidence: 90%
“…In just the same way, humans can learn to respond to either axis of variation in stimulus spaces involving dimensions that are clearly integral for them. Even nonanalytic systems can learn, gradually and associatively, to orient or reorient the decision boundary within a perceptual space, and thus they can sometimes respond undimensionally though implicitly (Wills et al, 2009). Though evidence consistent with attentional learning to dimensions by pigeons has been found (e.g., Mackintosh & Little, 1969), these results may sometimes be explained by invoking simpler and nonanalytic perceptual or associative processes.…”
Section: Discussionmentioning
confidence: 99%
“…Given that squirrels excel in object manipulation, it would not be surprising if squirrels perform better in a solid object colour discrimination–reversal learning task. Indeed, Wills et al (2009) examined three-dimensional colour and shape discrimination using solid objects and showed that squirrels could learn the task within 2 trials. A further possibility would be due to age: some studies have found that older individuals showed poorer performance in the reversal phase than younger individuals, to name a few, among rats (Brushfield et al 2008), beagle dogs (Tapp et al 2003) and rhesus monkeys (Bartus et al 1979; Rapp 1990).…”
Section: Discussionmentioning
confidence: 99%
“…All five squirrels went through pre-training that was similar to that used by Wills et al (2009) with pigeons; the pre-training was divided into four key stages, habituation, left or right side stimulus training, central stimulus training and hexagon training. In the habituation stage, intermittent food was delivered from both feeders unconditionally, allowing the squirrels to become habituated to obtaining food from them.…”
Section: Methodsmentioning
confidence: 99%